Race and Social Justice in If Beale Street Could Talk and If He Hollers Let Him Go - Hukelová, Martina (Univerzita Pardubice, 2023)
This thesis deals with racism and social justice portrayed in the novels If Beale Street Could Talk by James Baldwin and If He Hollers Let Him Go by Chester Himes. The thesis focuses on the literary and historical context of the novels as well as gender roles and religion in the United States during the 20th century. It also introduces the issue of structural and institutional racism. Besides discussing the theory, this thesis compares the two books.
Rasa a sociální spravedlnost v If Beale Street Could Talk a If He Hollers Let Him Go
Keywords: Africko-americká literatura; afro-americký feminismus; diskriminace; Druhá světová válka; feminismus; kolorismus; modernizmus; naturalizmus; otroctví; rasa; rasizmus; realismus; sociální nespravedlnost; zotročení; African-American literature; black feminism; colourism; discrimination; enslavement; feminism; modernism; naturalism; race; racism; realism; slavery; social injustice; Second World War